A topological framework for interactive queries on 3D models in the web - Figueiredo, Mauro (2017)
Submitted by CIAC Centro de Investigação em Artes e Comunicação (ciac@ualg.pt) on 2017-04-05T11:31:31Z No. of bitstreams: 1 920985.pdf: 3176704 bytes, checksum: a3bb1a7f08ef3073abaf8dbc99cf26d7 (MD5)